2002
DOI: 10.1002/cncr.10336
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fluorine‐18 fluorodeoxyglucose positron emission tomography and Ga‐67 scintigraphy in evaluation of lymphoma

Abstract: Ga-67 SPECT failed to demonstrate disease at 45 sites (35.7%). In 10 of 44 patients, Ga-67 SPECT completely failed to detect any disease at 22 of 45 sites (17.5%) and partially identified disease sites at 23 of 45 sites (18.2%) in 11 patients regardless of the tumor site and histology. In these patients, the lesions measured between 0.6 and 14.0 cm by CT. Fluorodeoxyglucose positron emission tomography revealed higher stage disease in 13 patients compared with Ga-67 imaging. Tumor-tobackground ratios were stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(24 citation statements)
references
References 34 publications
(38 reference statements)
0
23
0
1
Order By: Relevance
“…In comparisons of FDG PET and 67 Ga scintigraphy in the imaging of both HL and NHL, FDG PET consistently showed higher sensitivity than 67 Ga scintigraphy [4548]. In the late 1980s, the uptake of these two tracers was compared in five patients with NHL (the scans in two of these patients, patients 1 and 4, are shown in Fig.…”
Section: Clinical Imaging Of Lymphoma: Historical Overview and Currenmentioning
confidence: 99%
“…In comparisons of FDG PET and 67 Ga scintigraphy in the imaging of both HL and NHL, FDG PET consistently showed higher sensitivity than 67 Ga scintigraphy [4548]. In the late 1980s, the uptake of these two tracers was compared in five patients with NHL (the scans in two of these patients, patients 1 and 4, are shown in Fig.…”
Section: Clinical Imaging Of Lymphoma: Historical Overview and Currenmentioning
confidence: 99%
“…However, FDG-PET offers several advantages over Ga-67 imaging in the form of better dosimetry (lower radiation dose), quicker scans (1.5-2 h vs. 2-3 days or more), higher sensitivity (due to superior spatial resolution, lesser physiologic bowel uptake and better contrast resolution), better quantification potential (and hence better prognostic information) and superior assessment of response to therapy. [4651] FDG-PET imaging has an important role in all aspects of lymphoma workup: initial diagnosis, staging, grading, restaging (evaluation for recurrence or residual disease), assessing response to therapy and surveillance (especially for higher-stage disease initially). Lymphoma is perhaps the most frequent oncologic condition for which FDG-PET imaging is performed.…”
Section: Fdg-pet and Pet/ct In Oncologymentioning
confidence: 99%
“…Nonetheless, they have demonstrated that PET is at least equal and in many instances superior to other imaging techniques whether used singly or in combination. Although gallium-67 has a well recognised role in lymphoma PET has been demonstrated to be superior in comparative studies [21, 22]. An added advantage of PET is a more convenient imaging protocol coupled with its whole body imaging capability enabling simultaneous visualisation of nodal and extranodal sites.…”
Section: Stagingmentioning
confidence: 99%